PENGEMBANGAN MEDIA PEMBELAJARAN KOMIK UNTUK KETERAMPILAN BERBICARA: Development, Media, Speaking Skills - Saputri, Zohana Hanif; Firmansyah, Bayu (Jurnal Tinta, 2023)
This research started from the lack of variety of learning media in teaching and learning activities so it is necessary to develop a product in the form of comics as a learning medium. In the KD legend material. 311 and 4.11. The formulation of the problems contained in this study are: (1) How is the process of developing comic media for legend text speaking skills in seventh grade students of MTs Abu Amr. (This study aims to determine the process of developing comics media for legend text speaking skills in seventh grade students of MTs Abu Amr and the effectiveness of developing comic media for legend text speaking skills in seventh grade students of MTs Abu Amr. The research method used is Research and Development with the ADDIE model which includes 5 steps, namely analysis, design, development, implementation, evaluation. The results of the validation of 4 experts, namely 1 material expert, got an average score of 90% in the "Very Eligible" category, RPP experts got an average score of 95% in the "Very Eligible" category. Linguists get an average score of 93% in the "Very Eligible" category and Linguists get an average score of 95% in the "Very Eligible" category. Educator Response I got a score of 86% in the very decent category, educator II got a score of 84% in the very good category. The results of the speaking assessment test (retelling the contents of the legend) using comic media, students in the small group trial in class VII A got a score of 87% in the very good category, for the large group trial in class VII A got a score of 97% in the very good category.